Konsep Belajar Menurut Pandangan Islam - lndar, Djumberansyah (ULUL ALBAB Jurnal Studi Islam, 2001)
Islam teaching requires people to seek knowledge whenever and wherever they are. This is reflected on many hadists and verses of Al-Qur 'an. It is clearly stated that seeking knowledge is greatly pertinent for people in order that they are able to junction themselves as the chalifah. The process of learning can produce technology, which facilitates their lives.